Smart Blanket - Alias, Noor Rahmawati; Mohamad Razimi, Nur’Rabiatul Adawiyah; Zainal Abidin, Hasliza Hanim; Mustafa, Farah Nursarah; Abu Badri, Nurannisa Natasya (Academica Press Solutions, 2025)
The Smart Blanket project involves developing the already-existing sleeping technology through the building of a working prototype with temperature control, a sensor for tracking the index of health, and an easy-to-use interface for users. Functionality design is focused on energy, comfort, and compatibility with voice control devices like Google Assistant for smart sets. Some of the most critical outputs are increases in wellness, possibility to measure the wellbeing of the elderly, changing sleep risks, and increased comfort for the elderly use backed with strong health analytics. Efficiency in using energy and eco-friendly materials reinforces this product from claims of being a thread of sustainability to the environment and costs to the user. The key to developing a wide market for the vehicle, besides making overlays based on the principles of personalized comfort and smart elements, is the availability of its price. Safety, regulatory compliance as well as in-partite innovation based on the feedback from the user market are provided through adherence to the standards. All these combined will make the smart blanket a pioneering product in helping people sleep and improving their health.